Pathogenic LRRK2 requires secondary factors to induce cellular toxicity. Issue 10 (14th October 2020) - Lobbestael, Evy; Van den Haute, Chris; Macchi, Francesca; Taymans, Jean-Marc; Baekelandt, Veerle
Abstract: Pathogenic mutations in the leucine-rich repeat kinase 2 (LRRK2) gene belong to the most common genetic causes of inherited Parkinson's disease (PD) and variations in its locus increase the risk to develop sporadic PD. Extensive research efforts aimed at understanding how changes in the LRRK2 function result in molecular alterations that ultimately lead to PD. Cellular LRRK2-based models revealed several potential pathophysiological mechanisms including apoptotic cell death, LRRK2 protein accumulation and deficits in neurite outgrowth. However, highly variable outcomes between different cellular models have been reported. Here, we have investigated the effect of different experimental conditions, such as the use of different tags and gene transfer methods, in various cellular LRRK2 models. Readouts included cell death, sensitivity to oxidative stress, LRRK2 relocalization, α-synuclein aggregation and neurite outgrowth in cell culture, as well as neurite maintenance in vivo . We show that overexpression levels and/or the tag fused to LRRK2 affect the relocalization of LRRK2 to filamentous and skein-like structures. We found that overexpression of LRRK2 per se is not sufficient to induce cellular toxicity or to affect α-synuclein-induced toxicity and aggregate formation. Finally, neurite outgrowth/retraction experiments in cell lines and in vivo revealed that secondary, yet unknown, factors are required for the pathogenic LRRK2 effects on neurite length. Our findings stress the importance of technical and biological factors in LRRK2-induced cellular phenotypes and hence imply that conclusions based on these types of LRRK2-based assays should be interpreted with caution.